Individual choice in a residential building and heating model: An application case for Germany - Klaas Bauermann; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2015)
In Germany and other Central and Northern European countries, energy demand for space heating dominates the energy demand of households. In line with European and national energy efficiency and emission reduction objectives, policy makers have identified the residential building sector potentials for the achieving of reduction targets. This paper presents an extended logit model approach for the residential heating market with special regard to the development of the built environment and the heating system choice. A policy as usual scenario for Germany is calculated as an application example to evaluate the likeliness of target achievement for the heating market, its energy demand and associated emissions.
Keywords: Q42; Q48; 330; Discrete Choice; Heating Market; Policy Evaluation